Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Justice Charles Hamlin, Jim Christiansen, Justice Robert Martin 5080 E. Kings Canyon Road, Fresno